Case Report: Unusual Clinical Presentation of a Rare Cardiac Inflammatory Myofibroblastic Tumor in Children: The Differential Diagnosis With Pediatric Emergencies - Bilotta, Clio; Perrone, Giulio; Maresi, Emiliano; De Lisi, Giovanni; Di Pasquale, Pietro; Piro, Ettore; Argo, Antonina; Zerbo, Stefania (Frontiers in Pediatrics, 2021)
Introduction: There are still no guidelines about pediatric cardiac cancers. The purpose of this work is to provide new scientific data facilitating the differential diagnosis of a rare cardiac tumor with an unusual presentation, such as the cardiac inflammatory myofibroblastic tumor (IMT). Case presentation: A three-years-old male child presented with several symptoms including unconsciousness, vomit and drowsiness. A clinical and neurological examination revealed a unilateral (right) motor delay and positive unilateral Babinski sign. Electrocardiogram (ECG) was normal. Diagnostic Assessment: The total body Computed Tomography (CT) scans showed hypodensity in the left temporal-parietal lobe; a large hypodense area in the right frontal lobe and a second area in the left frontal lobe were found with head CT. A magnetic resonance (MR), also noted cerebral areas of hypointensity. The echocardiographic images revealed an ovoid mass, adherent to the anterolateral papillary muscle. The histological exams, performed with Hematoxylin-Eosin, Masson's Trichrome, Alcian Blue PAS, Weigert and Van-Gieson stain, allowed observing the microscopic structure of the neoplastic mass. The immunohistochemical analysis was performed through subsequent antibodies: anti-vimentin, anti-actina, anti-ALK, anti-CD8, anti-CD3. anti-CD20, anti-Kappa and Lambda chains and anti CD68 antibodies. The healthcare professionals diagnosed a cardiac IMT with brain embolism. Differential diagnosis: The ventricular localization, observed through radiological exams, required a differential diagnosis with fibroma and rhabdomyoma, the presence of brain embolism with sarcoma and its morphology with fibroma. Neurological symptoms might be attributed to encephalitis, primitive cerebral cancer, such as astrocytoma or neuroblastoma, cerebral metastases due to any malignancy, or embolic stroke. Conclusion: New studies are encouraged to better define IMT behavior and draw up guidelines confirming the crucial role of multidisciplinary approach and treatment protocol selected on the basis of tumors' characteristics, in the case of this rare type of cancer.